2011
DOI: 10.1038/bmt.2011.107
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients before and after haematopoietic stem cell transplantation measured with the European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Core Questionnaire QLQ-C30

Abstract: The EORTC Quality of Life Core Questionnaire QLQ-C30 is widely used, but no reference values are available for patients receiving HSCT. We retrieved data for 38 samples from 33 papers in English and German that provided evaluable information on QLQ-C30 scores (mean, s.d.) covering about 2800 patients. Results are presented as a table that provides reference data that allow QLQ-C30 scores at different points during the disease trajectory to be put in context. With respect to their central tendency and their var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
105
4
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(129 citation statements)
references
References 55 publications
(77 reference statements)
13
105
4
5
Order By: Relevance
“…8 However, there are several methodological problems with previous studies investigating RTW in SCT patients. First, many studies combine results from auto-and allo-SCT patients, 18,19 which is not optimal because the quality-of-life scores 20 and RTW rates seems to differ significantly between those groups. 7,21 Second, occupational status before SCT is either unknown 8,14,17,[22][23][24] or gathered just before the SCT, 18,19,21 which is misleading because many patients at that time point are on sick leave because of consolidation treatments.…”
Section: Introductionmentioning
confidence: 99%
“…8 However, there are several methodological problems with previous studies investigating RTW in SCT patients. First, many studies combine results from auto-and allo-SCT patients, 18,19 which is not optimal because the quality-of-life scores 20 and RTW rates seems to differ significantly between those groups. 7,21 Second, occupational status before SCT is either unknown 8,14,17,[22][23][24] or gathered just before the SCT, 18,19,21 which is misleading because many patients at that time point are on sick leave because of consolidation treatments.…”
Section: Introductionmentioning
confidence: 99%
“…22 In Brazil, studies using the QLQ-C30 indicate prevalence of fatigue, insomnia and loss of appetite, with fatigue being the most present and persistent symptom over time. 3,29 Loss of appetite was more intense in the autologous group in the pre-HSCT stage and in the allogeneic group in the post 100-day stage. However, the averages become equal in the post 180-day stage.…”
Section: Discussionmentioning
confidence: 97%
“…This study found that overall QoL is reduced during hospitalization, but it recovers to the baseline level up to one year after transplantation. 29 In Spain, a study that evaluated the QoL of 39 adult patients submitted to HSCT at the baseline, post two months and post nine months showed that general QoL is worse at two months compared to at baseline; however, it improves at nine months, thereby confirming a positive evolution throughout the therapeutic process. This same study makes a comparison between autologous and allogeneic HSCT, concluding that the type of transplantation did not influence QoL in the three stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 International guidelines recommend a multidisciplinary approach to supportive care and management of the organspecific complications of the chronic GvHD (cGvHD). 2 The main purpose of the treatment is to obtain the effective control of GvHD while minimizing the risk of drug toxicity and relapse.…”
Section: Introductionmentioning
confidence: 99%